Analisis Harga Saham Perbankan Sebelum dan Setelah Pengumuman Covid-19 di Indonesia - Fani Kristina (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2022)
This study aims to analyze banking stock prices before and after the announcement of Covid-19 in Indonesia. The stock price in this study uses the daily closing stock price. The sample was selected using purposive sampling technique. This study collected 5 national private foreign exchange banking companies listed in the ranking with the largest number of assets, namely Bank Central Asia Tbk, Bank Cimb Niaga Tbk, Bank Pan Indonesia Tbk, Bank OCBC NISP Tbk, and Bank Danamon Indonesia Tbk. Data were analyzed using the Wilcoxon Signed Rank Test. The analysis results show that there are significant differences in the stock prices of banking companies before and after the announcement of Covid-19 in Indonesia.